Can we achieve a balanced indoor environmental quality (ieq) in Malaysian historical museum building? - Sulaiman, R.; Kamaruzzaman, S.N.; Salleh, N.; Mahbob, N.S. (2011)
Indoor environment (IE) consists of indoor air, thermal, acoustic, visual or lighting, aesthetic, spatial and ergonomical quality. Each factor has its own parameters based on either quantitative or qualitative indicators according to acceptable numbers, ranges or characteristics. A balanced IE conditions in museum buildings refer to the preservation of cultural objects and the human comfort both the visitors and the staffs. The current situations of researches on IE control especially in museum environment are mainly focused in largely isolated ways which try to separate solution for each factor. To date, Malaysia has about 56 historical museum buildings where few studies have been done so far on the quality of their IE. This is something that needs close attention and therefore the aim of this paper is to look the IE issues in a holistic approach. Based on an ongoing research, this paper will discuss on the literatures framework in predicting risks in museum historical buildings due to poor IEQ.